Bi2S3 Bipyramids in Layered Sulfides M2Bi2S3(AlCl4)2 (M = Ag, Cu)12. Issue 2 (18th December 2014) - Groh, Matthias F.; Knies, Maximilian; Isaeva, Anna; Ruck, Michael
Abstract Black Cu2Bi2S3(AlCl4)2 and orange Ag2Bi2S3(AlCl4)2 were synthesized by solvent‐free reaction (polycrystalline powders) as well as in Lewis‐acidic ionic liquids (crystals) at temperatures of 200 °C or lower. X‐ray diffraction on single‐crystals of Cu2Bi2S3(AlCl4)2 revealed two centrosymmetric polytypes: a rhombohedral one, space group R<alternatives> <![CDATA[3]]> <inline-graphic xlink:href="ark:/27927/pgh3xswfbv0" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>c [a = 658.02(3) pm, c = 6794.3(3) pm], with six formula units in the unit cell (6R polytype), and a hexagonal one, space group P63/m [a = 658.71(6) pm, c = 2265.5(3) pm], with two formula units (2H polytype). Ag2Bi2S3(AlCl4)2 is homeotypic and crystallizes in the acentric hexagonal space group P<alternatives> <![CDATA[3]]> <inline-graphic xlink:href="ark:/27927/pgh3xswfc3c" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>2c with a = 691.65(3) pm, c = 2207.86(9) pm, and two formula units per unit cell (2H′ polytype). All structures consist of 2∞[(M+)2Bi2S3] layers (M = Cu, Ag) separated by double layers of AlCl4– tetrahedra and differ mainly in their stacking sequences and the orientation of the AlCl4– groups. The sulfidometalate layer is a honeycomb‐like network with M+ and S2– ions in plane, whereas pairs of Bi3+ cations occupy positions above and below the plane. The analysis of chemical bonding reveals strong covalent two‐center two‐electron bonds in the five‐atomic bipyramidal Bi2S3 unit (D3h symmetry) and covalent bonding with much higher ionic component to the coin metal cations. The DFT‐optimized shape of an isolated hypothetical Bi2S3 molecule differs only marginally from that in the layer. Hence, the compounds might be interpreted as Bi2S3 molecules embedded in MAlCl4 salts. Optical bandgaps of 1.6 eV (M = Cu) and 2.2 eV (M = Ag) were deduced from diffuse reflectance measurements. DFT‐based quantum chemical calculations indicate direct bandgaps of the same magnitude.